Pengembangan Buku Penuntun Praktikum Struktur dan Fungsi Tumbuhan dengan Model Argument-Driven Inquiry (ADI) - Zahra Mila Putri; Neni Hasnunidah; Berti Yolida (Universitas Lampung, 2018)
Practical guidebookswas one of the supporting implementation of practicum activities. This study aim was to produce practical guidebook of plant structure and function. The research design used was R D with 4-D model are: define, design, develop, disseminate, but disseminate stage not done. A practical guidebook product made using an attractive cover, Arial letters with size 12, and EYD are good and correct. Each worksheet consists of student identities, practical titles, theoretical basis, objectives, research questions, tools, materials, work steps, argumentation schemes, argument sessions, and reports. Expert and practitioner validation result was categorized